Transitivitas dalam Teks Peradilan Indonesia: Kajian Linguistik Fungsional Sistemik - Nidya Fitri; Ketut Artawa; Made Sri Satyawati; Sawirman Sawirman (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2021)
This article analyzes transitivity in Indonesian judicial texts, particularly Jessica-Mirna's judicial texts. Functional Systemic Linguistic (FSL) theory is used as an analytical tool. The data were collected through document recording with a qualitative descriptive method through the trial process from YouTube. The results of the trial process were transcribed into written data in the form of text. The data were analyzed in stages, namely, (1) classification of judicial text based on the content of the text; (2) text characteristics; (3) analysis using the LSF model. The results showed that the material process was obtained as much as 5,822 (45%) as the first order. The second place is occupied by mental processes obtained as much as 2,064 (15%). The third place is occupied by the forming process, obtained as much as 1,616 (11%). Based on the results of this study, the actions and deeds of the perpetrator were realized through the transitivity of Jessica-Mirna's judicial texts.